Lending Power : How Self-Help Credit Union Turned Small-Time Loans into Big-Time Change - Covington, Howard E., Jr., 1944- (Book collections on Project MUSE., 2017)
Established by Martin Eakes and Bonnie Wright in North Carolina in 1980, the nonprofit Center for Community Self-Help has grown from an innovative financial institution dedicated to civil rights into the nation's largest home lender to low- and moderate-income borrowers. Self-Help's first capital campaign--a bake sale that raised a meager seventy-seven dollars for a credit union--may not have done much to fulfill the organization's early goals of promoting worker-owned businesses, but it was a crucial first step toward wielding inclusive lending as a weapon for economic justice. In Lending Power journalist and historian Howard E. Covington Jr. narrates the compelling story of Self-Help's founders and coworkers as they built a progressive and community-oriented financial institution. First established to assist workers displaced by closed furniture and textile mills, Self-Help created a credit union that expanded into providing home loans for those on the margins of the financial market, especially people of color and single mothers.